SISTEM INFORMASI GEOGRAFIS UNTUK MONITORING KOORDINAT LAYANAN PELANGGAN DENGAN MENGGUNAKAN TEKNOLOGI OPENSTREETMAP - Khaerudin, Muhammad; Hendharsetiawan, Andy Achmad; Setiadi, Dedi; Sugiharto, Agus; Sumitra, Tata; Febrianto, Dannie; Al Din, Sayyid Jamal (Universitas Dirgantara Marsekal Suryadarma, 2024)
The washing business is currently growing at a very rapid rate, and to stay up with this expansion, the sector needs a solution that can improve data processing performance. Consumer and business data can be processed digitally, enabling systematization and organization in cases where the data can be physically represented and has precise location information. Customer coordinate mapping is one of the most recent advancements in customer service. There are many challenges when mapping the locations of consumers, particularly in a competitive company setting when clients are spread throughout several towns and subdistricts. Aside from regional issues and a labor shortage, another challenge is finding data sources. A customer service system is being developed using the OpenStreetMap (OSM) API, the HTML website framework, MySQL with Myadmin PHP capabilities, and OpenStreetMap API. OpenStreetMap (OSM) is a mapping platform that enables precise mapping. This is made possible by satellite imagery, which is available in almost all Indonesian residential areas. Furthermore, the digitization process is accelerated by OSM's task manager function, which divides the mapping region into smaller mapping blocks to enable multiple OSM contributors to map the same area simultaneously in multiple Indonesian districts and cities.